Anti-Inflammatory Effect of Ethanolic Extract of Carica Papaya Leaves and Indomethacin in Cotton Pellet Induced Granuloma in Animal Model - Sultana, Afroza; Afroz, Rumana; Yasmeen, Onayza; Aktar, Muqbula Tasrin; Yusuf, Md Abdullah (Journal of Current and Advance Medical Research, 2019)
Background: Anti-inflammatory effect can be exerted by Carica papaya. Objective: The purpose of the present study was to see the anti-inflammatory effect of ethanolic extract of Carica papaya leaves and indomethacin in carrageenan induced rat paw edema animal model. Methodology: This was an animal study carried out in the Department of Pharmacology at Dhaka Medical College, Dhaka, Bangladesh during the period from July 2014 to June 2015 for a period of one (01) year. The leaves of Carica Papaya collected from Botanical garden, Mirpur, Dhaka, Bangladesh. The animals were divided into four groups. The animals were divided into four groups. In all the animals granuloma were induced by implantation of autoclaved cotton pellet on the 1st day and they treated as follows: Group I were served as control that was received normal saline. Group II were received ethanolic extract of Carica Papaya leaves. Group III were received ethanolic extract of Carica Papaya leaves. Group IV were received indomethacin. On the 15th day animals were anesthetized, implanted pellets were dissected out, dried at hit air oven and the final weights were measured. Result: The experiment was carried out on 48 Long Evan Norwegian rats. Rats were divided in 4 groups of six animals each. The mean increase of weight of cotton pellet was 48.06±1.02, 24.48±0.36, 22.42±0.56 and 18.02±0.43 in group I, II, III and IV respectively. The inhibition of granuloma formation was 49.06%, 53.35% and 62.51% in group II, III and IV respectively. Conclusion: In conclusion the ethanolic extract of Carica Papaya leaves has effects on cotton pellet induced granuloma formation in experimental rat. Journal of Current and Advance Medical Research 2019;6(1):2-5